2021
DOI: 10.1007/s00508-021-01880-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological characteristics of COVID‑19 patients without comorbidities

Abstract: Objective To evaluate the clinical characteristics and detailed imaging features in coronavirus disease 2019 (COVID-19) patients without comorbidities.Material and methods This retrospective study included laboratory-confirmed and symptomatic COVID-19 patients without comorbid diseases who were admitted to our second level hospital between March 2020 and September 2020. We assessed the clinical, biochemical and imaging diagnostic parameters on admission. The patients were classified as non-severe and progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…However, patients without existing comorbidities have been neglected. Only small-scale studies (less than 200 patients) have reported the severity and mortality progression in populations without pre-existing comorbidities [ [35] , [36] , [37] , [38] ]. Based on a series of studies on COVID-19 in our group [ 7 , 8 , [31] , [32] , [33] , [39] , [40] , [41] ], we recognized that these patients without pre-existing disease also have specific traits and disease patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients without existing comorbidities have been neglected. Only small-scale studies (less than 200 patients) have reported the severity and mortality progression in populations without pre-existing comorbidities [ [35] , [36] , [37] , [38] ]. Based on a series of studies on COVID-19 in our group [ 7 , 8 , [31] , [32] , [33] , [39] , [40] , [41] ], we recognized that these patients without pre-existing disease also have specific traits and disease patterns.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study commenced at the beginning of the COVID-19 pandemic found that approximately 94% of the studied patients had residual disease on CT scans at discharge, with the most common persistent pattern being ground-glass opacities [ 21 ]. In these patients, however, the peak CT scores were predominantly at five days after hospital admission, in contrast with our findings or other research previously discussed where the scores peaked after ten days of hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of laboratory parameters indicative of acute inflammation (CRP), cell death (LDH), and hypercoagulable state (fibrinogen), showed good discrimination value for the development of critical COVID-19 in the derivation cohort, which was higher than any of the parameters alone. Our study is one of the very few available studies focusing on patients without pre-existing comorbidities [ 17 , 18 , 19 , 20 , 21 , 22 ] and, to the best of our knowledge, the first one that included patients who were uniformly treated with anticoagulants and corticosteroids/remdesivir in cases with oxygen desaturation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased LDH release in the circulation could reflect either direct infection of cells/tissues by SARS-CoV-2 or extensive tissue damage secondary to a strong systemic inflammatory response. Nevertheless, LDH seems to be an independent predictor for severe disease development and mortality consistently reported in patients without existing comorbidities [ 17 , 18 , 20 , 22 ], while it has not been included in COVID-19 risk scores such as the well-established 4C mortality score [ 2 ], which was developed based on mixed populations. This discrepancy further underlines the need to study patients without pre-existing comorbidities.…”
Section: Discussionmentioning
confidence: 99%